EARNING PER SHARE TERHADAP RETURN SAHAM DENGAN KEBIJAKAN DEVIDEN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SUB SEKTOR BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Indrawati, Indrawati; Alam, Syamsul; Djaharuddin, Dharmawati (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to determine Earning Per Share on Stock Return with Dividend Policy as an Intervening Variable in Coal Sub-Sector Companies Listed on the Indonesia Stock Exchange. Data collection uses secondary data obtained from financial statements using the purposive judgement sampling method with a total of 18 issuers, while the data units analyzed are 54 data units analyzed. The analysis used in hypothesis testing is panel data regression analysis with the help of Eviews 13 Software and the help of sobel test. The results of the study prove that Earning per Share (EPS) has a positive and significant effect on Stock Returns, Earning per Share (EPS) has a positive effect and is not significant to the Dividend Policy, the Dividend Policy has a negative effect on the Return of Shares, the Dividend Policy is not able to mediate the relationship between Earning per Share (EPS) and Return on Shares. Keywords : Earning Per Share, Dividend Policy, Stock Return